Significant Increase of Erectile Dysfunction in Men With Post-stroke: A Comprehensive Review - Zhao, Shankun; Wu, Weizhou; Wu, Panxing; Ding, Chao; Xiao, Bingxiang; Xu, Zhengbao; Hu, Yan; Shen, Maolei; Feng, Lu (Frontiers in Neurology, 2021)
Men with erectile dysfunction (ED) are considered to be at risk from stroke events. Conversely, post-stroke patients are also at high risk of ED, whereas a quantitative result from all the relevant studies has not been previously addressed. Therefore, we have performed a comprehensive review and meta-analysis on this issue. This study was registered on PROSPERO (ID No. CRD42021226618). Twenty studies with a total of 3,382 stroke events were included, of which six studies were included for quantitative analysis, and the remaining 14 studies were calculated for the ratio of ED. Synthetic results from four eligible studies providing the ED cases showed that stroke patients were associated with a significantly higher risk of ED than the general population [pooled relative risk (RR) = 3.32, 95% confidence interval (CI): 1.25–8.82, P = 0.016]. Men with stroke were also found to be associated with a significant decline in International Index of Erectile Function −5 (IIEF-5) score as compared with the healthy controls [three studies, standard mean differences (SMD) = −1.8, 95% CI: −2.94 to −0.67, P = 0.002]. The prevalence of ED in post-stroke patients among 14 studies ranged from 32.1 to 77.8%, which was dramatically higher than that of the general population. The result of the GRADE-pro revealed that the quality of the evidence in this study was moderate. The present study has confirmed the high prevalence of ED in men with stroke. ED in stroke patients is a result of both neurological and psychological factors. Rehabilitative interventions rather than phosphodiesterase-5 (PDE-5) inhibitors are recommended to improve the erectile function for those survivors with ED.